Redefining educational leadership in Central Asia : selected cases from Kazakhstan and Kyrgyzstan - Tajik, Mir Afzal; Makoelle, Tsediso Michael (Emerald Publishing Limited, 2024)
Educational institutions within the post-soviet independent states of Kazakhstan and Kyrgyzstan have seen dramatic changes and educational reforms since their independence. Rapid technological changes, economic globalization, and increased migration and mobility of students have led Central Asian states to reform their education systems, within both secondary schools and higher education institutions such as universities. As a result, there is an increasing emphasis on redefining and reconceptualizing the role of leadership to better facilitate and lead the reform process. Providing a research-based account on the educational reforms taking place in these countries, Redefining Educational Leadership in Central Asia brings together the voices, views, experiences, and reflections of educational leaders from both secondary schools and higher education institutions in Kazakhstan and Kyrgyzstan. The chapters provide useful insights into the fundamental educational reforms shaping school leadership in Kazakhstan and Kyrgyzstan, educational leadership policies and practices, the myths and realities of school development planning and university leaders'performance in the higher education system of Kyrgyzstan. This is a new and unique perspective on educational leadership and the first of its kind to focus on Kazakhstan and Kyrgyzstan from a non-western perspective. Policymakers, researchers, graduate students, and practitioners will be able to draw from the strategic visions offered while reviewing and revisiting leadership policies and practices in the climate of rapid changes and heightened expectations from these leaders.
Includes index.
Keywords: Educational leadership -- Asia, Central.; Education -- Leadership.; Educational administration and organization.; Educational strategies and policy.; elektronické knihy; electronic books